The Effect of “Si Andi” Flashcard Games on Improving Personal Safety Skills - Maritza, Erra Khanza; Scarvanovi, Berliana Widi (JURNAL PENDIDIKAN USIA DINI, 2024)
One of the highest and continually increasing phenomena of violence in Indonesia is sexual abuse. The most frequent victims of this phenomenon are early childhood. The purpose of this study is to determine the influence of the "SI ANDI - Siap Amankan Diri” (Ready to Protect Yourself) flashcard games on improving personal safety skills in early childhood. This study involved 40 subjects aged 4-6 years, divided into control and experimental groups (n=20 for each group). This research is a quasi-experimental study with a non-equivalent control group design. Assessment of personal safety skills employed the WIST-III instrument. The hypothesis was analyzed using independent sample t-tests. The "SI ANDI" flashcard games program was effective on improving personal safety skills among participants in the experimental group, as evidenced by a statistically significant p-value of sig. 0.000 < 0.005. This finding suggests that the "SI ANDI" flashcard games can be used as an alternative tool for teaching personal safety skills in early childhood. Further observation is necessary to ascertain the long-term effects of using the "SI ANDI - Siap Amankan Diri" flashcards on the personal safety skills of young children. This is essential for identifying changes that occur over an extended period, providing insight into the sustained impact of the intervention. Keywords: personal safety skills; sexual abuse; early childhood; sex education References: Agudo, J. E., Rico, M., & Sánchez, H. (2016). Design and Assessment of Adaptive Hypermedia Games for English Acquisition in Preschool. Journal of Universal Computer Science, 22(2), 161–179. Agustina, L. S. S., Kusumawati, R. N., & Hardjono. (2022). Edukasi Seks Berbasis Permainan Puzzle untuk Meningkatkan Keterampilan Perlindungan Diri Anak. 14(2), 49–61. https://doi.org/10.15294/intuisi.v14i2.29575 Akbar, Z., & Mudzdaliffah, F. (2012). Program Pendidikan Seks Untuk Meningkatkanproteksi Diri Dari Eksploitasi Seksual Pada Anak Usia Dini. Perspektif Ilmu Pendidikan, 25(XV1), 1–6. https://doi.org/10.21009/PIP.251.1 Akl, E. A., Sackett, K. M., Pretorius, R., Bhoopati, P. S. S., Mustafa, R., Schünemann, & Erdley, W. S. (2009). Educational games for health professionals. William S, 1. https://doi.org/10.1002/14651858.CD006411.pub2. Andayani, R. P., Afnuhazi, R., Dafris, S., Huda, P. R., Ningsih, Y. H. D., Irwanda, B., Edo, C. W. D., Oka Surya, D., Guslinda, G., & Syofia Sapardi, V. (2022). Implementasi Personal Safety Skill Untuk Mencegah Kekerasan Seksual Pada Anak Sekolah Dasar. Jurnal Abdi Mercusuar, 2(2), 51–58. https://doi.org/10.36984/jam.v2i2.324 Anggraini, T., Sofia, A., & Riswandi. (2017). Pendidikan Seksual Anak Usia Dini: Aku dan Diriku. Jurnal Pendidikan Anak, 3(2). Anggreni, P. F., Asri, I. G. A. A. S., & Ganing, N. N. (2017). Pengaruh Model Pembelajaran Kooperatif Tipe Think-Pair-Share ( Tps ) Berbantuan Media Kartu Bergambar Terhadap Penguasaan Kompetensi Pengetahuan Ips Siswa Kelas V Gugus Letkol Wisnu. Mimbar PGSD, 5(2), 1–10. https://doi.org/doi.org/10.23887/jjpgsd.v5i2.10645 Angreany, F., & Saud, S. (2017). Keefektifan Media Pembelajaran Flashcard Dalam Keterampilan Menulis Karangan Sederhana Bahasa Jerman Siswa Kelas Xi Ipa Sma Negeri 9 Makassar. Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 1(2), 138–146. https://doi.org/10.26858/eralingua.v1i2.4410 Arbianingsih, Rustina, Y., Krianto, T., & Ayubi, D. (2018). Developing a health education game for preschoolers: What should we consider? Enfermería Clínica, 28, 1–4. https://doi.org/10.1016/S1130-8621(18)30025-1 Arsyad, A. (2015). Media Pembelajaran. PT Raja Grafindo Persada. Azizah, S., Khuzaemah, E., & Lesmanawati, I. R. (2017). Penggunaan Media Internet eXe-Learning Berbasis Masalah pada Materi Perubahan Lingkungan untuk Meningkatkan Hasil Belajar Siswa. Scientiae Educatia, 6(2), 197. https://doi.org/10.24235/sc.educatia.v6i2.1957 Azzahra, Q. M. (2020). Pendidikan Seksual Anak Usia Dini:" My Bodies Belong To Me". Early Childhood: Jurnal Pendidikan, 4(1), 77–86. Bagley, C., & King, K. (2004). Child Sexual Abuse: The Search for Healing. Boyle, C. L., & Lutzker, J. R. (2005). Teaching young children to discriminate abusive from nonabusive situations using multiple exemplars in a modified discrete trial learning format. 20, 55–69. Brown-Goodyear, & Paris. (2012). Handbook of child sexual abuse: Identification, assessment and treatment. John Wiley and Sons. Buttner, A. (2013). Aktivitas Permainan Dan Strategi Penilaian Untuk Kelas Bahasa Asing. PT Indeks. Çeçen-Eroğul, A. R., & Hasirci, Ö. K. (2013). The Effectiveness of Psycho-educational School-based Child Sexual Abuse Prevention Training Program on Turkish Elementary Students. Educational Sciences: Theory and Practice, 13(2), 725–729. Dames, I., Koeswanti, H. D., & Radia, E. H. (2019). Penerapan Model Examples Non Examples Berbantuan Media Gambar untuk Meningkatkan Hasil Belajar pada Tema 1 Siswa Kelas 5 SDN Sidorejo Lor 05 Salatiga. Jurnal Basicedu, 709–715. https://doi.org/10.31004/basicedu.v3i2.59 Doman, G., & Doman, J. (2006). How to Teach Your Baby to Read. Square One Publishers. Duma, S. (2017). Behavior skills training untuk meningkatkan personal safety skills sebagai prevensi terhadap kekerasan seksual pada anak [Doctoral Dissertation]. Universitas Sumatera Utara. Fajriani, D. A., Adjie, N., & Putri, S. U. (2022). Media Flashcard Untuk Menstimulus Perkembangan Kognitif Anak Usia 5-6 Tahun. In Prosiding Seminar Nasional PGPAUD UPI Kampus Purwakarta, 1, 56–68. Finkelhor, D. (2009). The Prevention of Childhood Sexual Abuse. The Future of Children, 19(2,), 169–194. Fitriyani, E., & Nulanda, P. Z. (2017). Efektivitas Media Flash Cards dalam Meningkatkan Kosakata Bahasa Inggris. Psympathic : Jurnal Ilmiah Psikologi, 4(2), 167–182. https://doi.org/10.15575/psy.v4i2.1744 Hasanah, A., Rahayu, S. R., & Kuswardinah, A. (2019). The Effect of Parenting, Teacher’s Role, and Peers on Children’s Personal Safety Skills in Tangerang. Public Health Perspectives Journal, 4(3), 164–170. Hatiningsih, N., & Adriyati, P. (2019). Implementing Flashcard to Improve the Early Reading Skill. Proceedings of the 4th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2018). Proceedings of the 4th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2018), Surat Thani, Thaland. https://doi.org/10.2991/acpch-18.2019.71 Herayanti, L., Fuadunnazmi, M., & Habibi. (2017). Pengembangan Media Pembelajaran Berbasis Moodle Pada Matakuliah Fisika Dasar. Jurnal Cakrawala Pendidikan, 36(2), 210–219. Holis, A. (2016). Belajar Melalui Bermain untuk Pengembangan Kreativitas dan Kognitif Anak Usia Dini. Jurnal Pendidikan UNIGA, 09(01), 23–37. Hotimah, E. (2017). Penggunaan media flashcard dalam meningkatkan kemampuan siswa pada pembelajaran kosakata bahasa Inggris kelas II MI Ar-Rochman Samarang Garut. Jurnal Pendidikan UNIGA, 04(01), 10–18. Humaira B, D., Rohmah, N., Rifanda, N., Novitasari, K., Diena H, U., & Nuqul, F. L. (2015). Kekerasan Seksual Padaanak: Telaah Relasi Pelaku Korban Dan Kerentanan Pada Anak. Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 12(2), 5. https://doi.org/10.18860/psi.v12i2.6398 Hurlock, E. B. (2006). Perkembangan Anak Jilid II. Erlangga. Irfan, M., Rahman, A., & Jannah, M. (2023). Pengaruh Penggunaan Media Flashcard Terhadap Pengetahuan tentang Pencegahan Kekerasan Seksual pada Siswa SD Inpres Unggulan Toddopuli Kecamatan Panakkukang Kota Makassar. Jurnal Publikasi Pendidikan, 1–9. Jatmikowati, T. E., Angin, R., & Ernawati, E. (2015). Model Dan Materi Pendidikan Seks Anak Usia Dini Perspektif Gender Untuk Menghindarkan Sexual Abuse. Jurnal Cakrawala Pendidikan, 3(3). https://doi.org/10.21831/cp.v3i3.7407 Juarni, S. E., Mukhtar, D. Y., & Daulay, D. A. (2020). Knowledge and Personal Safety Skill of Children in Banda Aceh. International Research Journal of Advanced Engineering and Science, 5(1), 60–62. Kemenpppa. (2023). SIMFONI PPA (Sistem Informasi Online Perlindungan Perempuan dan Anak) [dataset]. https://kekerasan.kemenpppa.go.id/ringkasan Kendall, P. C. (2012). Child and Adolescent Therapy: Cognitive-Behavioral Procedures. The Guildford Press. Kenny, M. C. (2009). Child Sexual Abuse Prevention: Psychoeducational Groups for Preschoolers and Their Parents. The Journal for Specialists in Group Work, 34(1), 24–42. https://doi.org/10.1080/01933920802600824 Khadijah. (2016). Pengembangan Kognitif Anak Usia Dini. Perdana Publishing. Kumalasari, D., & Kurniawati, F. (2018). The Effectiveness of Behavioral Skills Training (BST) Program to Improve Personal Safety Skills for Down syndrome Adolescent with Mild Intellectual Disability. Psychological Research on Urban Society, 1(2), 81. https://doi.org/10.7454/proust.v1i2.28 Kupzyk, S., Daly, E. J., & Andersen, M. N. (2011). A Comparison Of Two Flash-Card Methods For Improving Sight-Word Reading. Journal of Applied Behavior Analysis, 44(4), 781–792. https://doi.org/10.1901/jaba.2011.44-781 Mashudi, E. A., & Nur’aini. (2015). Pencegahan Kekerasan Seksual Pada Anak Melalui Pengajaran. 9(2), 60–71. https://doi.org/10.17509/md.v9i2.3253 Neherta, M. (2017). Modul Intervensi pencegahan kekerasan seksual terhadap anak. Padang: Universitas Andalas. Nida, D. M. A. A., Parmiti, D. P., & Sukmana, A. I. W. I. Y. (2020). Pengembangan Media Kartu Bergambar Berorientasi Pendidikan Karakter Pada Mata Pelajaran Bahasa Bali. Jurnal Edutech Undiksha, 8(1), 16. https://doi.org/10.23887/jeu.v8i1.25393 Noviana, I. (2015). Kekerasan Seksual terhadap Anak: Dampak dan Penanganannya. Sosio Informa, 1(1), 13–28. Nurrita, T. (2018). Pengembangan Media Pembelajaran Untuk Meningkatkan Hasil Belajar Siswa. MISYKAT: Jurnal Ilmu-ilmu Al-Quran, Hadist, Syari’ah dan Tarbiyah, 3(1), 171. https://doi.org/10.33511/misykat.v3n1.171 Papalia, D. E., & Feldman, R. D. (2008). Psikologi Perkembangan (edisi terj). Kencana Prenada Media Group. Paramastri, I., Supriyati, & Priyanto, M. A. (2010). Early Prevention Toward Sexual Abuse on Children. JURNAL PSIKOLOGI, 37(1), 1–12. Probosiwi, R., & Bahransyaf, D. (2015). Pedofilia Dan Kekerasan Seksual: Masalah Dan Perlindungan Terhadap Anak. Sosio Informa, 1(1), 29–40. Rahmawati, A. (2014). Metode Bermain Peran dan Alat Permainan Edukatif untuk Meningkatkan Empati Anak Usia Dini. Jurnal Pendidikan Anak, 3(1), 382–392. https://doi.org/10.21831/jpa.v3i1.2875 Saadah, B., & Yulia, C. (2022). Efektivitas Media Flashcard Untuk Meningkatkan Pemahaman Sex Education Pada Siswa. Research and Development Journal of Education, 8(2), 572. https://doi.org/10.30998/rdje.v8i2.13622 Safitri, R. W., Primiani, C. N., & Hartini, H. (2018). Pengembangan media flashcard tematik berbasis permainan tradisional untuk kelas IV sub tema lingkungan tempat tinggalku. Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 8(1), 1. https://doi.org/10.25273/pe.v8i1.1332 Santrock, J. W. S. (2007). Perkembangan Anak Jilid 1 Edisi Kesebelas. PT Erlangga. Sarno, J. A., & Wurtele, S. K. (1997). Effects of a personal safety program on preschoolers’ knowledge, skills, and perceptions of child sexual abuse. Child Maltreatment, 2(1), 35–45. https://doi.org/10.1177/1077559597002001004 Seniati, L., Yulianto, A., & Setiadi, B. N. (2011). Psikologi Eksperimen. PT Indeks. Setiawati, N. L. M., Dantes, N., & Candiasa, I. M. (2015). Pengaruh Penggunaan Media Gambar Flash Card Terhadap Minat dan Hasil Belajar IPA Peserta Didik Kelas VI SDLBB Negeri Tabanan. Jurnal Penelitian Dan Evaluasi Pendidikan Indonesia, 5(1). https://doi.org/doi.org/10.23887/jpepi.v5i1.1549 Silvia, K. S., & Wirabrata, I. D. G. F. (2021). Meningkatkan Kosakata Anak Usia Dini Melalui Media Wordwall. Jurnal Pendidikan Anak Usia Dini Undiksha, 9(2), 261. https://doi.org/10.23887/paud.v9i2.36814 Sugiyono. (2014). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Penerbit Alfabeta. Sujiono, Y. N. (2009). Konsep Dasar Pendidikan Anak Usia Dini. Indeks. Sulistiani, S. L. (2016). Konsep Pendidikan Anak Dalam Islam Untuk Mencegah Kejahatan Dan Penyimpangan Seksual. Ta’di Jurnal Pendidikan Islam, 5(1), 99–107. https://doi.org/10.29313/tjpi.v5i1.1998 Sulistiyowati, A., Matulessy, A., & Pratikto, H. (2018). Psikoedukasi Seks untuk Mencegah Pelecehan Seksual pada Anak Prasekolah. Jurnal Ilmiah Psikologi Terapan, 6(1), 17–27. https://doi.org/10.22219/jipt.v6i1.5171 Sunismi. (2015). Developing Guided Discovery Learning Materials Using Mathematics Mobile Learning Application As An Alternative Media For The Students Calculus II. Jurnal Cakrawala Pendidikan, 3(3). https://doi.org/10.21831/cp.v3i3.7340 Tampubolon, G. N., Nurani, Y., & Meilani, S. M. (2019). Pengembangan Buku Pendidikan Seksual Anak Usia 1-3 Tahun. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(2), 527. https://doi.org/10.31004/obsesi.v3i2.243 Topping, K. J., & Barron, I. G. (2009). School-based child sexual abuse prevention programs: A review of effectiveness. Review of Educational Research, 79(1), 431–463. https://doi.org/10.3102/0034654308325582 Umar, N. M., Noviekayati, I., & Saragih, S. (2018). Efektivitas Personal Safety Skill terhadap Peningkatan Kemampuan Mencegah Kekerasan Seksual pada Anak Ditinjau dari Jenis Kelamin. Indigenous: Jurnal Ilmiah Psikologi, 3(1), 45–50. https://doi.org/10.23917/indigenous.v3i1.5815 Utami, N. T. (2023). Meningkatkan Kognitif Anak Usia Dini melalui Media Flashcard. Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 6(01), 43–52. https://doi.org/10.46963/mash.v6i01.692 Van Stolk, M. (1978). The battered child in Canada. McLelland & Stewart. Wahyuni, F., & Azizah, S. M. (2020). Bermain dan Belajar pada Anak Usia Dini. Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 15(01), 161–179. https://doi.org/10.37680/adabiya.v15i01.257 Walsh, K., Zwi, K., Woolfenden, S., & Shlonsky, A. (2018). School-Based Education Programs for the Prevention of Child Sexual Abuse: A Cochrane Systematic Review and Meta-Analysis. Research on Social Work Practice, 28(1), 33–55. https://doi.org/10.1177/1049731515619705 Wasilah, E. B. (2012). Peningkatan Kemampuan Menyimpulkan Hasil Praktikum Ipa Melalui Penggunaan Media Kartu. 1(1), 82–90. Wati, I. K., & Oka, I. G. (2021). Penggunaan Flash Card dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris Peserta Didik. Indonesian Gender and Society Journal, 1(2), 41–49. https://doi.org/10.23887/igsj.v1i2.39081 Widiarsini, N. M. P., Ujianti, P. R., & Magta, M. (2021). Development of Picture Card Learning Media to Improve Sexual Understanding in Group B Kindergarten Children. Indonesian Journal Of Educational Research and Review, 4(1), 17–25. Widyati, W. (2014). Belajar dan Pembelajaran Perspektif Teori Kognitivisme. BIOSEL (Biology Science and Education), 3(2), 177–187. http://dx.doi.org/10.33477/bs.v3i2.521 Wulandari, M. D., Widhayanti, A., Hidayat, M. T., Fathoni, A., & Abduh, M. (2019). Identifikasi Pengetahuan Dan Keterampilan Perlindungan Diri Anak Dari Pelecehan Seksual Di Sd Muhammadiyah 1 Surakarta. Profesi Pendidikan Dasar, 1(1), 61–68. https://doi.org/10.23917/ppd.v1i1.8374 Wurtele, S. K. (2008). Behavioral approaches to educating young children and their parents about child sexual abuse prevention. The Journal of Behavior Analysis of Offender and Victim Treatment and Prevention, 1(1), 52–64. https://doi.org/10.1037/h0100434 Wurtele, S. K., Hughes, J., & Owens, J. S. (1998). An Examination of the Reliability of the “What If” Situations Test: A Brief Report. Journal of Child Sexual Abuse, 7(1), 41–52. https://doi.org/10.1300/J070v07n01_03 Wurtele, S. K., & Miller-Perrin, C. L. (1993). Preventing child sexual abuse: Sharing the responsibility: Vol. Vol 2. U of Nebraska Press. Zulfa, E. R., & Djamali, F. (2018). Pengaruh Permainan Flash Card Terhadap Kemampuan Membaca Pada Siswa Usia 4-6 Tahun Di Ra Ar-Ridlwan Ajung Jember Tahun Ajaran 2015/2016. JECIE (Journal of Early Childhood and Inclusive Education), 1(2), 136–144.